ANALISIS FRAMING PEMBERITAAN PILGUB JATENG PADA HARIAN MERDEKA. - Adi Nugroho (JURNAL ILMU SOSIAL, 2009)
Analysis of Framing Suara Merdekan Daily, Mei-June 2008 editions is try to look how political news in local media, specifically in general election of Central Java Governoor 2008 (Pilgub Jateng 2008). Research concerning Suara Merdeka Daily Mei-June 2008 edition about news political. The Framing Analysis want to look how the candidate’s popularity seems to appear on the news paper in high frequency.